Acid base and blood gas analysis in term neonates immediately after birth with uncomplicated neonatal transition - Nariae Baik-Schneditz; Bernhard Schwaberger; Berndt Urlesberger; Christina Helene Wolfsberger; Marlies Bruckner; Gerhard Pichler (BMC, 2022)
Abstract Background Acid base and blood gas measurements provide essential information, especially in critically ill neonates. After birth, rapidly changing physiology and difficulty to obtain blood samples represent unique challenges. Objectives The aim of the present study was to establish normal values of capillary acid base and blood gas analysis immediately after birth in term neonates after uncomplicated neonatal transition. Method This is a post-hoc-analysis of ancillary outcome parameter of a prospective observational study in term neonates immediately after caesarean section. Neonates were included after immediate neonatal transition without need of medical support and a capillary blood sample was taken by a heel-stick within 15-20 minutes after birth. Result One hundred thirty-two term neonates were included with mean (SD) gestational age of 38.7 ± 0.7 weeks. The blood was drawn mean (SD) 16 ± 1.7 minutes after birth. The mean (SD) values of the analyses were: pH 7.30 ± 0.04, pCO2 52.6 ± 6.4, base excess − 0.9 ± 1.7 and bicarbonate 24.8 ± 1.6. Conclusion This is the first study describing acid base and blood gas analyses in term neonates immediately after birth with uncomplicated neonatal transition.